Professionals’ Responses to Aggravated Intimate Partner Violence - Ingrid Løining Ørum (Bergen Journal of Criminal Law and Criminal Justice)
How are professionals in Norway responding to the pervasive issue of intimate partner violence (IPV)? Under Norwegian law, the duty to avert (DTA) obliges all citizens, including professionals, to act against intimate partner violence, distinguishing it from legislation on mandatory reporting (MR) as it allows – and demands – averting by reporting to the police or by other means. There is a lack of insight into the usage of the duty to avert among professionals dealing with intimate partner violence.